2019
DOI: 10.2147/ndt.s208361
|View full text |Cite
|
Sign up to set email alerts
|

<p>Depression and associated factors among patients with tuberculosis in Ethiopia: a cross-sectional study</p>

Abstract: Purpose The study aimed to assess the magnitude of depression and associated factors among patients with tuberculosis (TB) visiting outpatient clinics in Ethiopia. Patients and methods A cross-sectional study was conducted among 415 TB patients. Study participants were selected through a systematic random sampling technique. Patient Health Questionnaire-9 (PHQ-9) was used to assess depression using face-to-face interviews. Data were analyzed using SPSS version 20. Bivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
34
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 30 publications
8
34
2
3
Order By: Relevance
“…We did not find an association between HIV comorbidity and mental disorders in our sample. This finding is in agreement with some studies, (32, 33) but not others. (13,34) Studies that reported an association between comorbidity and mental disorders have posited HIV-associated stigma as the plausible driving force.…”
Section: Discussionsupporting
confidence: 94%
“…We did not find an association between HIV comorbidity and mental disorders in our sample. This finding is in agreement with some studies, (32, 33) but not others. (13,34) Studies that reported an association between comorbidity and mental disorders have posited HIV-associated stigma as the plausible driving force.…”
Section: Discussionsupporting
confidence: 94%
“…We did not find an association between HIV comorbidity and mental disorders in our sample. This finding is in agreement with some studies (32,33) , but not others (13,34) . Studies that reported an association between co-morbidity and mental disorders have posited HIV-associated stigma as the plausible driving force (13,34) .…”
Section: Discussionsupporting
confidence: 94%
“…Approximately 26 % of enrolled TB patients had PHQ-9 scores indicative of moderate to severe depression and 15 % indicative of suicidal ideation. Our estimate was comparable to recent studies in several countries that examined depression (moderate to severe) among TB patients, including Ethiopia (17•6-54•0 %) (32)(33)(34) , South Africa (32•9 %) (13) , Angola (49•4 %) (35) and China (18•1 %) (36) . They were, however, considerably lower than those found in Ethiopia using PHQ-9 by Ambaw et al (32) ; these differences may have arisen from variations in study location and population.…”
Section: Discussionsupporting
confidence: 87%
“…The characteristics of the study populations included in this study are depicted in Table 1. Out of 25 studies included in the review, seven were from Pakistan [15,[26][27][28][29][30][31], seven from India [32][33][34][35][36][37][38], three from Nigeria [18,39,40], four from Ethiopia [11,19,41,42], one from Brazil [43], one from China [44], one from Cameron [45], and one from Turkey [47]. The studies included in this review were published between 2006 and 2019, with the sample size ranging between 45 participants in India and 1252 participants in China.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%